2015
DOI: 10.1515/ract-2014-2314
|View full text |Cite
|
Sign up to set email alerts
|

Research of thermodynamic and kinetics in preparing U(IV) by reducing and catalyzing U(VI) with hydrazine

Abstract: The effect of concentration of U(VI), hydrazine, nitric acid and the amount of catalyst, and the thermodynamics and kinetics of the reaction in preparing U(IV) by catalyzing and reducing U(VI) are studied in catalytic reduction of U(VI) with hydrazine as reductant and Pt as catalyst. The comparison of calculated theoretical reaction heat value and practical value is also given. The result shows that with the increase of density of U(VI) and hydrazine, increase of amount of catalyst and decrease of nitric acid,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…It was reported that formic acid reduced U(VI) to U(IV) much faster than hydrazine. Xia et al .reported kinetic and thermodynamics of U(VI) reduction with N 2 H 4 over platinum black catalyst material [28] . In this study Xia et al .…”
Section: Introductionmentioning
confidence: 66%
See 3 more Smart Citations
“…It was reported that formic acid reduced U(VI) to U(IV) much faster than hydrazine. Xia et al .reported kinetic and thermodynamics of U(VI) reduction with N 2 H 4 over platinum black catalyst material [28] . In this study Xia et al .…”
Section: Introductionmentioning
confidence: 66%
“…The rate of U(VI) reduction by hydrazine over Pt/SiO 2 can be described by the reaction shown in equation 9. [28] true-dC()UO22+dt=k[[UO22+]​1.1N2H4]​1.4[H+]​0.7 …”
Section: Response Surface Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…Their electrochemical characteristics can be modulated through changing the combinations of anions and cations without upsetting the balance. [ 20,21 ] They are widely considered as one of the most promising green solvents [ 22,23 ] for various applications such as catalysis, [ 24,25 ] separation science, [ 26–28 ] synthesis (or reaction medium), [ 29–34 ] electrochemistry, [ 35–37 ] and energy storage. [ 38–42 ] The wide liquid phase range, high heat resistance, low vapor pressure, wide electrochemical windows, and high ionic conductivity make them highly desirable as electrolytes in various battery systems (i.e., LIBs, sodium‐ion batteries (SIBs), potassium‐ion batteries (PIBs), magnesium‐ion batteries (MIBs), zinc‐ion batteries (ZIBs), aluminum‐ion batteries (AIBs), metal–air, [ 43–45 ] metal–sulfur, [ 46–49 ] and metal–oxygen [ 50 ] ).…”
Section: Introductionmentioning
confidence: 99%